import proveit
theory = proveit.Theory() # the theorem's theory
from proveit import A, B
from proveit.logic import Not, in_bool, FALSE
%proving false_antecedent_implication
Prove $A$ assuming $\bot$ via deriving a contradiction.
F_assuming_F = FALSE.prove(assumptions=[FALSE])
not_a_impl_F = F_assuming_F.as_implication(Not(A))
A_via_contradiction = not_a_impl_F.derive_via_contradiction(assumptions=[in_bool(A)])
Now we can derive $\bot \Rightarrow A$ via Deduction.
A_via_contradiction.as_implication(FALSE)
%qed